Research on the dependence relationship and the dynamic evolution in the carbon emission trading system of China - Wu, Xianbo; Hui, Xiaofeng; Cao, Jiwen (Frontiers in Environmental Science, 2025)
As the world’s largest developing country and the large economy with carbon emission, China has opened 8 markets for carbon emission trading. This article uses the method of information entropy to study the dependence relationship within China’s carbon emission trading system from 2017 to 2021, and characterizes the core structure and dynamic evolution process of this dependence relationship. Research has found that, firstly, there is a broad dependence among the 8 carbon emission trading markets in China, and this dependence is changing with the process of economic development. Especially after China proposed the carbon peaking and carbon neutrality goals in 2020, the correlation between the 8 carbon markets has been significantly strengthened. Secondly, China’s carbon market presents a north-central-south distribution pattern, and the carbon market in the south is more important, which is also in line with the pattern of China’s economic development. Finally, the carbon market in Guangdong province has a higher level of development nationwide and plays an important role in China’s carbon emission trading system. This province has two carbon emission markets, namely the Shenzhen market and the Guangdong market, which are at the core of China’s carbon market system. This is closely related to the economic development level and industrial development model of Guangdong province. Based on the above conclusions, this study suggests that China’s carbon market can start from economically underdeveloped regions, fully leverage the latecomer advantages of these regions, and gradually introduce derivative products such as carbon futures in the development of the carbon spot market, improving the liquidity and effectiveness of the carbon market while avoiding the risks of the carbon spot market. Meanwhile, a reasonable determination of carbon market prices also requires the joint efforts of the market and the government.